Identifikasi Fitoplasma pada Wortel (Daucus carota L.) dan Wereng yang Berasosiasi dengan Penyakit Kuning di Bogor dan Bandung, Jawa Barat - Wulandari, Isti; Hamzah Mutaqin, Kikin; Giyanto, Giyanto; Hendrastuti Hidayat, Sri (Jurnal Fitopatologi Indonesia, 2022)
Identification of Phytoplasmas on Carrot (Daucus carota L.) and Leafhopper Associated with Yellow Disease in Bogor and Bandung, West JavaYellow symptoms similar to phytoplasma infection were found in carrot fields in West Java. This study aims to identify phytoplasma from carrot and leafhoppers associated with yellow symptoms in Bogor and Bandung, West Java. Five species of leafhoppers, i.e. Balclutha incisa (Matsumura), Orosius argentatus (Evans), Cicadulina bipunctata (Matsumura), Empoascanara indica (Datta), Exitianus indicus (Distant), and 1 species of planthopper, i.e. Sogatella  furcifera (Horváth) were found in carrot plants in Bogor. Phytoplasma detection in plants and insects was carried out by nested-PCR, sequencing, and DNA sequencing analysis. Nested-PCR successfully amplified target DNA, i.e. 16S rRNA phytoplasma gene from plants and insects. Sequence analysis based on identity matrix showed the highest homology of samples from Bogor with the phytoplasma from the 16SrII group, i.e. Peanut witches’-broom phytoplasma; while the sample from Bandung showed the highest homology with the phytoplasma of the 16SrI group, i.e. Ca. Phytoplasma asteris and Tomato big bud phytoplasma. Sequence analysis of phytoplasma from B. incisa and S. furcifera showed the highest homology with phytoplasma from the 16SrII group, i.e. Cactus witches’-broom phytoplasma; while the phytoplasma from C. bipunctata showed the highest homology with the 16SrI group of phytoplasma, i.e. Ca. Phytoplasma asteris. This paper is the first report of phytoplasma infecting carrots in Bogor and Bandung, West Java.